1998
DOI: 10.1085/jgp.111.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signaling Mediates Stimulation of L-Type Ca2+ Current Elicited by Withdrawal of Acetylcholine in Cat Atrial Myocytes

Abstract: A perforated-patch whole-cell recording method was used to determine whether nitric oxide signaling participates in acetylcholine (ACh)-induced regulation of basal L-type Ca 2� current (I Ca,L ) in cat atrial myocytes. Exposure to 1 �M ACh for 2 min inhibited basal I Ca,L (�21 � 3%), and withdrawal of ACh elicited rebound stimulation of I Ca,L above control (80 � 13%) (n � 23). Stimulation of I Ca,L elicited by withdrawal of ACh (but not ACh-induced inhibition of I Ca,L ) was blocked by either 50 �M hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
53
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 43 publications
15
53
2
Order By: Relevance
“…By this mechanism, NO signaling mediates the stimulation of I Ca,L elicited by ACh withdrawal. 8 These findings are consistent with studies in chick heart cells, in which ACh withdrawal stimulates cAMP above control levels. 14 Others laboratories have reported that ACh withdrawal stimulates I Ca,L in Purkinje fibers 15 and ventricular myocytes prestimulated by ␤-adrenergic agonists.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…By this mechanism, NO signaling mediates the stimulation of I Ca,L elicited by ACh withdrawal. 8 These findings are consistent with studies in chick heart cells, in which ACh withdrawal stimulates cAMP above control levels. 14 Others laboratories have reported that ACh withdrawal stimulates I Ca,L in Purkinje fibers 15 and ventricular myocytes prestimulated by ␤-adrenergic agonists.…”
supporting
confidence: 90%
“…7 In cat atrial myocytes, AChinduced inhibition of basal L-type Ca 2ϩ current (I Ca,L ) is not mediated by NO signaling. 8 However, ACh withdrawal stimulates I Ca,L above control levels, ie, rebound stimulation, and this response is mediated by NO signaling. 8,9 The rebound stimulation of I Ca,L elicited by ACh withdrawal results in stimulation of atrial contraction, 9 atrial pacemaker activity, 10 and the potential development of Ca 2ϩ -mediated delayed afterdepolarizations and arrhythmic atrial activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…W7 (10 M) inhibited MAPK (ERK 1, 2) and CREB phosphorylation by 80.9, 69.5, and 71.0%, respectively, whereas H89 (10 M) reduced the degree of phosphorylation by 67.2, 67.7, and 55.0%, respectively. For determinations of involvements of these molecules, the concentrations of inhibitors used in this study were referred to these articles (Wang et al, 1998;Grewal 2000a,b). On the other hand, the protein kinase C (PKC) inhibitor GF109203X (1 M) did not affect ␤-eudesmol-induced MAPK activation (data not shown).…”
mentioning
confidence: 99%